Penyelesaian Sengketa Keolahragaan dan Kepastian Hukum Dalam Sistem Hukum Indonesia - Wahyunitha, Agnes; Wijaya, Andika; Nugraha, Satriya (JURNAL USM LAW REVIEW, 2026)
This study aims to examine the legal protection of professional basketball athletes and coaches through employment contracts and to assess their alignment with Law Number 11 of 2022 concerning Sports. Using a normative juridical method with statutory and conceptual approaches, this research analyzes the role of employment contracts as preventive legal instruments and evaluates the effectiveness of sports dispute resolution mechanisms. The findings show that although the Sports Law has strengthened the normative framework and promoted arbitration-based dispute resolution, its implementation remains limited due to weak contract standardization and overlapping authority between sports arbitration bodies and general courts. This situation undermines legal certainty and the finality of arbitration decisions. The study emphasizes the importance of strengthening contractual clauses on welfare protection, injury compensation, termination, and mandatory sports arbitration to ensure substantive justice. It concludes that better synchronization between sports law, contract law, and dispute resolution mechanisms is essential to enhance legal certainty for professional basketball practitioners in Indonesia. Penelitian ini bertujuan untuk menganalisis perlindungan hukum bagi atlet dan pelatih bola basket profesional melalui perjanjian kerja serta mengkaji kesesuaiannya dengan Undang-Undang Nomor 11 Tahun 2022 tentang Keolahragaan. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan dan konseptual untuk menilai fungsi kontrak kerja sebagai instrumen perlindungan hukum preventif serta efektivitas mekanisme penyelesaian sengketa olahraga. Hasil penelitian menunjukkan bahwa meskipun UU Keolahragaan telah memperkuat kerangka normatif dan mendorong penyelesaian sengketa melalui arbitrase, implementasinya masih terkendala oleh lemahnya standarisasi kontrak dan tumpang tindih kewenangan antara arbitrase olahraga dan peradilan umum. Kondisi ini berdampak pada berkurangnya kepastian hukum bagi atlet dan pelatih. Penelitian ini menegaskan pentingnya penguatan klausula kontrak kerja dan sinkronisasi mekanisme penyelesaian sengketa guna menjamin keadilan substantif bagi pelaku olahraga bola basket di Indonesia.